Effect of psychostimulant medications on static balance performance in adults with attention deficit hyperactivity disorder: Within-subjects repeated-measure study - Alotaibi, Mansour M.; Motl, Robert W.; Stavrinos, Despina; Snyder, Scott W.; Singh, Harshvardhan; Lein, Donald H. (Human movement science, 2023)
This study examined the effect of psychostimulant medications nPS) on balance and functional motor performance in adults with attention-deficit/hyperactivity disorder (ADHD). Participants completed two sessions (off-medication and on-medication) in a within-subjects repeated-measure study design. There was a minimum of seven days between the two sessions. During both sessions, participants stood for 30 s per condition on a force platform. The conditions were: feet-apart with 1) eyes-open and 2) eyes-closed; feet-together with 3) eyes-open and 4) eyes-closed. Participants performed three trials of timed up and go (TUG) and lateral step-up test (LSUT) during both sessions. Outcome measures were sway area (SA [cm2]), average sway velocity (SV [cm/s]), TUG average time (s), and average number of LSUT repetitions. Data were analyzed using multivariate repeated measures analysis of variance and paired t-tests for examining PS effects on balance (SA and SV) and functional motor performance (TUG and LSUT), respectively. The sample included 45 adults (35 females; mean age = 28.4 ± 6.3 years). The repeated-measures MANOVA indicated that PS was associated with better SA [F(1,44) = 9.6; p = 0.003;ηp2 = 0.18] but not with SV [F(1,44) = 1.0; p = 0.319;ηp2 = 0.02]. PS was associated with significantly better SA with decreasing base-of-support [F(1,44) = 9.9; p = 0.003;ηp2 = 0.18]. Additionally, PS use was associated with better TUG [t(1,44) = 2.65; p = 0.014;Cohen's d = 0.39] but not LSUT performances [t(1,44) = −0.68; p = 0.499;Cohen's d = −0.10]. PS was associated with better SA and TUG in adults with ADHD. Further studies are needed to investigate the effects of PS on balance performance using rigorous designs in this population. Healthcare providers should screen for PS status and balance when treating adults with ADHD to enhance safe motor performance.